2021
DOI: 10.3389/fpsyg.2021.689162
|View full text |Cite
|
Sign up to set email alerts
|

Large Gatherings? No, Thank You. Devaluation of Crowded Social Scenes During the COVID-19 Pandemic

Abstract: In most European countries, the first wave of the COVID-19 pandemic (spring 2020) led to the imposition of physical distancing rules, resulting in a drastic and sudden reduction of real-life social interactions. Even people not directly affected by the virus itself were impacted in their physical and/or mental health, as well as in their financial security, by governmental lockdown measures. We investigated whether the combination of these events had changed people's appraisal of social scenes by testing 241 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Subjective discomfort ratings increased in concert with the observed increases in personal space size in the current study. These findings are broadly consistent with other evidence for discomfort with the physical proximity of others during the pandemic, such as higher arousal ratings and more negative appraisals of images depicting large social gatherings during the early pandemic ( Massaccesi et al, 2021 ). The time course of this discomfort response (i.e., the length of time it may take to abate after the most threatening aspects of the pandemic, related to the risks for serious illness, death, or loss, have substantially lessened) remains unclear.…”
Section: Discussionsupporting
confidence: 89%
“…Subjective discomfort ratings increased in concert with the observed increases in personal space size in the current study. These findings are broadly consistent with other evidence for discomfort with the physical proximity of others during the pandemic, such as higher arousal ratings and more negative appraisals of images depicting large social gatherings during the early pandemic ( Massaccesi et al, 2021 ). The time course of this discomfort response (i.e., the length of time it may take to abate after the most threatening aspects of the pandemic, related to the risks for serious illness, death, or loss, have substantially lessened) remains unclear.…”
Section: Discussionsupporting
confidence: 89%
“…Some researchers claim that social restrictions may increase the craving for social touch in the same way that fasting increases the craving for food (e.g., Ujitoko et al, 2022, Von Mohr et al, 2021). Others argue that the social restrictions dictated by COVID-19 have changed how humans perceive touch, such that touch is now perceived as a threat signal that may even generalize into reduced positive reactions to observed touch (Massaccesi et al, 2021). Our results support the second argument and are in line with a study by Massaccesi et al (2021), which demonstrated that images depicting crowds and large gatherings were rated as less positive during the pandemic period compared to the pre-pandemic period.…”
Section: Discussionmentioning
confidence: 99%
“…Others argue that the social restrictions dictated by COVID-19 have changed how humans perceive touch, such that touch is now perceived as a threat signal that may even generalize into reduced positive reactions to observed touch (Massaccesi et al, 2021). Our results support the second argument and are in line with a study by Massaccesi et al (2021), which demonstrated that images depicting crowds and large gatherings were rated as less positive during the pandemic period compared to the pre-pandemic period. Moreover, participants who reported overall greater physical isolation, stronger feelings of social closeness and higher perceived threat of COVID-19 gave more positive ratings to images depicting individuals alone and in very small groups.…”
Section: Discussionmentioning
confidence: 99%
“… Unless otherwise specified, the language for each scale was English. Italy Sample 1, Germany, and Austria were drawn from Massaccesi et al (2021) . …”
Section: Methodsmentioning
confidence: 99%
“…Reactance questions measured the degree to which participants felt angry that their governments were Unless otherwise specified, the language for each scale was English. Italy Sample 1, Germany, and Austria were drawn from Massaccesi et al (2021).…”
Section: Political Beliefs: Governmental Response To Coronavirus Ques...mentioning
confidence: 99%